Intrathecal Dexmedetomidine: A Study of its Postop Analgesic Effects When Used as an Adjuvant in Elective C-Section Surgery under Spinal Anesthesia - Muhammad Saadat Ali, Rahila Aamir, Tehzeeb Zehra, Zainab Fareed, Muhammad Waseem Rabbani, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Despite the advances in anesthesiology and surgical techniques, postoperative pain continues to be a global health-care issue. To increase the duration of analgesia during caesarian section under spinal anesthesia, adjuvants are frequently added to improve the quality of block. Aim: To determine the mean post-operative duration of analgesia produced by intrathecal dexmedetomidine with bupivacaine as compared to bupivacaine with placebo in patients undergoing elective caesarean section in spinal anesthesia. Study Design: Randomized control trial Place and Duration of Study: Department of Anaesthesiology and Gynaecology/Obstetrics Operation Theatre, Nishtar Medical University, Multan from 1st July 2020 to 31st December 2020. Methodology: Sixty patients admitted for elective caesarean section were randomized into two groups. Subarachnoid block was performed in all the patients. Group D received intrathecal Inj. Dexmedetomidine 10 mcg along with the standard bupivacaine dose while group C received 1 ml of 0.9% isotonic saline. Time for requirement of first rescue analgesia, which was provided by Inj. Ketoroloac 30 mg IV noted. Results: The mean post-operative analgesia of Group D and Group C was 270.25±23.81 minutes and 140.46±10.38 minutes, respectively in statistically significant difference( p=0.000). Post stratification was applied to control the effect modifiers like age, BMI, parity and ASA. It was found that in all strata of patients, Dexmedetomidine provided statistically significant difference in analgesia as compared to control group (p=0.000). Conclusion: Standard spinal anesthesia with Dexmedetomidine has a longer duration of post-operative analgesia as compared to standard spinal anesthesia alone.